Cold Love (2015-05-12) - Dupre, Lonnie; University of Minnesota Duluth. Royal D. Alworth, Jr. Institute for International Studies (2015)
Introduction and post-film discussion by Lonnie Dupre Filmmaker, Minnesota Adventurer & Arctic Explorer. The first person to make a winter-time ascent of Mt. Denali, North America's highest peak. A film about the dramatic beauty and life- giving forces of our earth's frozen places, as well as the fragile state of its health. Royal D. Alworth, Jr. Institute for International Studies, UMD Sustainability, the League of Women Voters Duluth, and the Duluth Parent Teacher Student Association Council